43. THE CURRENT STATUS OF HUMAN RESOURCES MANAGEMENT AT THE HO CHI MINH CITY CENTER FOR DISEASE CONTROL IN 2024 (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the current status of human resources management at the Ho Chi Minh city Center for Disease Control in 2024.Materials and methods: A cross-sectional descriptive study was conducted to examine the human resources management practices at Ho Chi Minh city Center for Disease Control. Data were collected through surveys regarding personnel management within the center.Results: The Ho Chi Minh city Center for Disease Control currently employs a total of 430 staff members, of whom 254 are female and 176 are male. The majority (82.09%, 353 people) are employed under permanent contracts. The largest proportion of staff holds positions in medical and related professional fields, representing 71.86% of the workforce. Approximately 18% of the employees have post-graduate qualifications. According to Circular 03/2023/TT-BYT issued by the Ministry of Health, there is a need to supplement 139 additional personnel. The existing policies in place at the center have shown a positive impact on human resources management.Conclusion: The current human resources at Ho Chi Minh city Center for Disease Control are insufficient to meet both the actual demand and the requirements stipulated by Circular 03/2023/TT-BYT of the Ministry of Health.
Keywords: Human resources management; healthcare workforce; Ho Chi Minh city Center for Disease Control